Building automation: Photovoltaic assisted thermal comfort management system for energy saving - Khan M.R.B.; Jidin R.; Pasupuleti J.; Shaaya S.A. (Institute of Physics Publishing, 2023)
Building automation plays an important key role in the means to reduce building energy consumption and to provide comfort for building occupants. It is often that air conditioning system operating features ignored in building automation which can result in thermal discomfort among building occupants. Most automation system for building is expensive and incurs high maintenance cost. Such system also does not support electricity demand side management system such as load shifting. This paper discusses on centralized monitoring system for room temperature and photovoltaic (PV) output for feasibility study of PV assisted air conditioning system in small office buildings. The architecture of the system consists of PV modules and sensor nodes located at each room. Wireless sensor network technology (WSN) been used for data transmission. The data from temperature sensors and PV modules transmitted to the host personal computer (PC) wirelessly using Zigbee modules. Microcontroller based USB data acquisition device used to receive data from sensor nodes and displays the data on PC. Published under licence by IOP Publishing Ltd.